2013
DOI: 10.1002/ajmg.b.32142
|View full text |Cite
|
Sign up to set email alerts
|

Testing the diathesis‐stress model: 5‐HTTLPR, childhood emotional maltreatment, and vulnerability to social anxiety disorder

Abstract: Regarding the development of social anxiety disorder (SAD), a diathesis-stress paradigm including biological vulnerabilities and environmental stressors can be assumed. However, studies dealing with the etiology of SAD did not integrate both aspects so far. We examined a particular diathesis-stress model for SAD in which we included a functional polymorphism of the serotonin transporter (5-HTTLPR) as a genetic vulnerability factor and childhood emotional maltreatment (CEM) as an environmental stressor. Current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The triallelic 5‐HTTLPR genotype proportions (L A L A , n = 1881; L A L G , n = 480; SL A , n = 2962; L G L G , n = 58; SL G , n = 394; SS, n = 1262) were not in Hardy–Weinberg equilibrium ( P = 0.001). However, the proportion of L A (51%), L G (7%), and S (42%) alleles were similar to the proportions found in a previous Danish study (Rasmussen, Bagger, Tanko, Christiansen, & Werge, ) and the distribution according to transcriptional activity (high: 27%, intermediate: 49%, low: 24%) resembles previous observations in Northern European populations (Araya et al., ; Bukh et al., ; Reinelt et al., ).…”
Section: Methodssupporting
confidence: 90%
“…The triallelic 5‐HTTLPR genotype proportions (L A L A , n = 1881; L A L G , n = 480; SL A , n = 2962; L G L G , n = 58; SL G , n = 394; SS, n = 1262) were not in Hardy–Weinberg equilibrium ( P = 0.001). However, the proportion of L A (51%), L G (7%), and S (42%) alleles were similar to the proportions found in a previous Danish study (Rasmussen, Bagger, Tanko, Christiansen, & Werge, ) and the distribution according to transcriptional activity (high: 27%, intermediate: 49%, low: 24%) resembles previous observations in Northern European populations (Araya et al., ; Bukh et al., ; Reinelt et al., ).…”
Section: Methodssupporting
confidence: 90%
“…Similarly, for participants with SAD, most of the evaluated studies ( n = 5 [3,7,21,43,61]) indicated a higher prevalence of EETs in the SAD group compared with the control group. An exception was one study [43], which found no differences between the groups with respect to physical and sexual traumas.…”
Section: Resultsmentioning
confidence: 99%
“…To conduct a meta-analysis of emotional trauma and ADs, six studies [3,21,43,61,67,71] were analyzed and no evidence of publication bias was found among these studies (P > 0.05).…”
Section: Emotional Traumamentioning
confidence: 99%
“…31 Anxiety spectrum disorders are triggered by stressors related with life events that cause fear of loss of control and seem to be associated with childhood trauma, particularly emotional abuse and parental rejection. 32,33 Quality stress factors that predispose to anxiety disorders in young population appear to be more related to fear of loss of health or destabilization in the parental environment (health problems, financial hardship, parental hostility). 34 History of child abuse is considered a risk factor for the appearance of both anxiety disorders and depression 32 for individuals who are exposed to the stressful military environment.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Quality stress factors that predispose to anxiety disorders in young population appear to be more related to fear of loss of health or destabilization in the parental environment (health problems, financial hardship, parental hostility). 34 History of child abuse is considered a risk factor for the appearance of both anxiety disorders and depression 32 for individuals who are exposed to the stressful military environment. The onset of depressive symptomatology is associated with life events related to the loss of an important person or change in life role.…”
Section: Discussionmentioning
confidence: 99%